Evaluation of floristic and structural aspects of an Araucaria Forest fragment influenced by successive rotations of exotic forest species (Revista de Ciências Agroveterinárias, 2015)
In Santa Catarina State, Brazil, wood exploitation and the expansion of agricultural areas represent some of the responsible factors for the significant reduction of natural areas. The objective was to provide information on the floristic composition and the structure of a remnant forest in order to subsidize the restoration of degraded areas. Sampling was performed by the method of quadrant points, where we measured the diameter of the plant to the lap height (individuals from 1 meter to 1.30 meters in height), the diameter at breast height (individuals over 1.30 meters), and the distance from the base (point central); the frequency, density, and absolute and relative dominance, the importance value index, the Shannon diversity, and the Pielou evenness were calculated. To evaluate the floristic-structural similarity between transects we used the Bray-Curtis index, performed by the ordination of transects on the basis of floristic characteristics through multivariate analysis technique NMDS. The study found 254 arboreal individuals belonging to 17 families, 20 genders and 36 species. The species with the highest importance value were: Baccharis uncinella, Solanum variabile, Mimosa scabrella, Pinus taeda, and Vernonanthura discolor. The diversity index was 2.56 nats. ind-1 and the evenness was 0.69, indicating low ecological dominance in the area. According to the assessment of the similarity between transects, it was possible to observe the separation of two distinct floristic groups through greater similarity of transects 1-3 and 2-4. The NMDS analysis indicated that the floristic-structural organization of regenerating component showed no marked spatial variations associated with the environmental characteristics of each transect. The results follow the standard found in studies conducted in similar areas and that the maintenance of these forest fragments favors the formation of biodiversity corridors.
Keywords: permanent preservation areas; riparian vegetation; phytosociological; Pinus.